Chemical and Physical Properties of Natural Zeolites and Their Potential Industrial Applications - T. H. Eyde (The Minerals, Metals and Materials Society, 1981)
Several hundred natural zeolite deposits occur in Tertiary and Cretaceous age formations of the western United States. Most of the large deposits are altered vitroclastic tuffs. Many of these deposits consist of a matrix of a high purity zeolite mineral or minerals in which fragments of unaltered rock are imbedded. These deposits represent an extensive resource of zeolite minerals which can be beneficiated to a consistently uniform, high quality product. The beneficiated natural zeolite products will possess many advantages over the selectively mined, unbeneficiated natural products currently being produced. These advantages will include: uniform particle size, high purity, consistent quality, high brightness, low iron content, high attrition resistence, uniform cation exchange and adsorption capacities, and low price.